2015
DOI: 10.1007/s10640-015-9971-4
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Fish for Higher Profits? Price Response and Economic Incentives in Global Tuna Fisheries Management

Abstract: This paper evaluates industry-wide economic incentives arising from changes in product prices in an industry exploiting a common renewable resource (tropical tunas) that is regulated via output limits. Changes in prices alter economic incentives by affecting revenues, profits, conservation, and nonmarket public benefits. Economic incentives in industries exploiting common resources have been examined from multiple angles. However, industry level variation in market prices arising from changes in public regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Elasticity of demand estimates for FAD free tuna depend upon the market segment, consumer environmental concerns, and availability of substitutes. Estimates indicate that elasticity is close to 1, implying that total revenues would not change (Sun et al 2017;Sun et al 2015). The three payment options could be combined to assemble the required amounts.…”
Section: The Tradeoffs Of Coasean-style Exchangementioning
confidence: 99%
“…Elasticity of demand estimates for FAD free tuna depend upon the market segment, consumer environmental concerns, and availability of substitutes. Estimates indicate that elasticity is close to 1, implying that total revenues would not change (Sun et al 2017;Sun et al 2015). The three payment options could be combined to assemble the required amounts.…”
Section: The Tradeoffs Of Coasean-style Exchangementioning
confidence: 99%
“…The literature on the effect of consumer preference for species rarity on the rate of extraction is scant. There are a few studies demonstrating that consumer preference for species rarity retains the level of consumption even at exaggerated market prices (Gault et al ., 2008; Sun et al ., 2017). However, a strong preference for rarity alone is not sufficient to generate an anthropogenic Allee effect (Harris et al ., 2013).…”
Section: Rarity Value and Species Extraction From The Wildmentioning
confidence: 99%
“…[22], Holt [35] and Sun et al . [33][36] considerations leads to an alternative formulation by introducing new parameters d 1 and d 2 .…”
Section: A General Synthetic Inverse Demand System Approachmentioning
confidence: 99%
“…The demand system itself is subject to several ex-ante decisions on the part of the analyst concerning the appropriate market delineation (the limits of the relevant market). Several recent studies have shown strong globalization of the tuna markets [3740] [33] and identified two separate market chains: purse-seine/cannery-grade and long-line/sashimi-grade tuna markets [41] [42] [9] [36]. Each of the two distinct markets, purse-seine/cannery-grade and long-line/sashimi-grade, are highly integrated at the global level by both price and commodity flows across locations and species, making any regional change in catches important to the entire industry.…”
Section: A General Synthetic Inverse Demand System Approachmentioning
confidence: 99%
See 1 more Smart Citation